Enhancing Financial Quality: Impact of Accounting Information Systems, Internal Control with Company Performance as Moderating Factor - Rachman, Andini Dwi Mega; Asaari, Masagus (Research of Accounting and Governance, 2025)
This research aims to determine the effect of accounting information systems and internal control systems on the quality of financial reports with company performance as a moderator. The primary data used in this research was obtained directly from statements (questionnaires) of PT employees. Sources of Alfaria Trijaya Tbk and secondary data in this research were obtained from the official website of PT. Source Alfaria Trijaya Tbk. The results of this research show that There is a significant influence of the accounting information system on the quality of financial reports; There is a significant influence of the internal control system on the quality of financial reports; There is a significant influence of the accounting information system on the quality of financial reports moderated by company performance; There is a significant influence of the internal control system on the quality of financial reports moderated by company performance. The contribution of this study lies in the identification and in-depth analysis of the influence of accounting information systems and internal control systems on the quality of financial reports, with company performance as a moderating factor. Managerial implications highlight the critical role of robust accounting information and internal control systems in ensuring high-quality financial reporting